Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/nau.20380
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term efficacy of group pelvic floor training under intensive supervision versus unsupervised home training for female stress urinary incontinence: A randomized pilot study

Abstract: Group PFMT under intensive supervision produced significantly better improvements in primary and secondary outcomes in the short-term compared to individual, unsupervised home application of PFMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 29 publications
4
61
1
16
Order By: Relevance
“…PFM function assessment by the PERFECT system took place monthly for training adjustments and progression. 18 No additional resources were addressed for treating OAB syndrome symptoms in addition to PFMT.…”
Section: Pfm Training Protocolmentioning
confidence: 99%
“…PFM function assessment by the PERFECT system took place monthly for training adjustments and progression. 18 No additional resources were addressed for treating OAB syndrome symptoms in addition to PFMT.…”
Section: Pfm Training Protocolmentioning
confidence: 99%
“…57 157,162,190 assignment based on hospital casenote number 116 or assignment based on time of arrival at the clinic and severity of incontinence. 127 Allocation concealment was also considered to be suboptimal (sealed envelopes with no indication of third party involvement) in a further five studies.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…Description of studies 115 and full text reports of these trials had already been identified in the SR. 116,117 b This was a new trial but also picked up by SR MEDLINE search shortly after -related to timing of searches. 118 c Replaces National Research Register.…”
Section: Chaptermentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, é razoável supor que os efeitos do tratamento serão melhores se o programa de TMAP, além de ser baseado em princípios fisiológicos confiáveis e de garantir uma contração perineal correta antes do início da realização dos exercícios, contar com estreita supervisão e apoio dos profissionais de saúde envolvidos para manter a adesão ao tratamento 26 . Suposição essa que, apesar de ter sido confirmada em estudo prévio 27 , não encontrou respaldo nos resultados de uma revisão sistemática 28 sobre a eficácia dos exercí-cios para o AP no tratamento da IU e nos resultados do presente estudo, visto que, apesar de o aumento da FMP ter sido significantemente superior no Gsup, não houve diferença significativa entre os resultados do Gsup e do Gobs quanto à IU.…”
Section: Discussionunclassified